2007
DOI: 10.1016/j.hrthm.2006.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Regional left atrial voltage in patients with atrial fibrillation

Abstract: BACKGROUND-Regional differences in fibrosis, particularly related to the posterior wall and septum, may be important in atrial fibrillation (AF). Using electroanatomic mapping, voltage can be used as a measure of fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 19 publications
(6 reference statements)
2
80
1
1
Order By: Relevance
“…This is also consistent with previous reports, which suggest a regional distribution of structural defects in AF patients-most often affecting the LAPW and septum. 5,11,13 In ≈90% of our patients, voltage maps demonstrated reproducibility of LVAs. Previously undetected LVAs may indicate disease progression in the LVA group, whereas new LVAs were not detected in previously healthy atria.…”
Section: Lvas and Structural Substrate In The Atriummentioning
confidence: 55%
See 1 more Smart Citation
“…This is also consistent with previous reports, which suggest a regional distribution of structural defects in AF patients-most often affecting the LAPW and septum. 5,11,13 In ≈90% of our patients, voltage maps demonstrated reproducibility of LVAs. Previously undetected LVAs may indicate disease progression in the LVA group, whereas new LVAs were not detected in previously healthy atria.…”
Section: Lvas and Structural Substrate In The Atriummentioning
confidence: 55%
“…11 Oakes et al 5 have shown that LA fibrosis and scar tissue detected by delayed enhancement cardiac MRI correlate well with LVAs on voltage maps. We found significant LVAs within the LA in 47 patients (27% overall and 35% in patients with persistent AF).…”
Section: Lvas and Structural Substrate In The Atriummentioning
confidence: 96%
“…Recent studies have shown that, in comparison to conventional PVI, PVI with the addition of voltage-guided substrate modification achieved by targeting the lowvoltage area is more effective, is safer, and leads to lower proarrhythmic potential [9][10][11][12][13] . A measurement of < 0.5 mV was used in several previous studies as the criterion for identifying low-voltage areas indicative of interstitial fibrosis in the right and left atria [14][15][16] in the setting of SR or atrial pacing. Furthermore, both Malcolme-Lawes et al and Oaks et al showed that LA voltage < 0.5mV during SR corresponds to LA fibrosis identified by delayed enhancement magnetic resonance imaging (MRI) 17,18) .…”
Section: La Voltages During Sr and Afmentioning
confidence: 99%
“…Pre-existent left atrial (LA) scars indicated by low-voltage zones (LVZs) on 3-dimensional (3D) electroanatomic maps are implicated in suboptimum ablation outcomes 7,8) , and success has been achieved in patients with PerAF when, in addition to PVI, the atrial substrate has been modified by ablation of low-voltage areas detected during sinus rhythm (SR) [9][10][11][12][13] . Slight differences exist between the definitions of such low-voltage zones (LVZs), which are described variously as areas of bipolar voltage of < 0.4 mV ~ < 0.5 mV, depending on the group of investigators [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Potentials with amplitudes >0.5 mV were defined as normal and coded in purple color, and potentials <0.2 mV as low voltage coded in red or gray. 30,31 In low voltage areas highdensity mapping was performed to delineate them from the high voltage areas. The interpolation was adjusted to 15 in both NavX and Carto cases.…”
Section: Catheter Ablation Proceduresmentioning
confidence: 99%